Islam and Mantaining Ecological Health - Fini Fajrini; Triana Srisantyorini; Ernyasih Ernyasih; Dina Fadlilah; Iswan Iswan (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2022)
The environment provides various resources for humans and other living things that inhabit it. Soil, water and air are 3 important components that support life and life on the earth’s surface. In the Qur’an it is stated that the creation of the heavens and the earth as well as various natural resources such as wind (air), water, plants and animals is a mercy from Allah for humans. The environment is a gift given by Allah SWT. to all His creatures to be used, guarded and preserved properly. This is done as a form of concern to manifest a sense of love and affection for Allah’s creation. Islam teaches about environmental maintenance which must be implemented in human attitudes and behavior so as not to cause damage to the earth.Muslim scientists in the era of the Caliphate had paid so much attention to ecology and health. Islamic scholars at that time thought that ecological changes could have an impact on human health. Muslim doctors in the heyday of Islamic civilization have conducted studies on environmental pollution that causes various diseases. Some Muslim scientists in the golden age of Islam who have studied the relationship between Islam Habl min Allah, habl min an-nas, and habl min al-alam, are concepts of human relations regulated by the Qur’an. These three are the guidelines and demands given by God to humans in their life in the world. The role of the caliph given by Allah to humans must include all three. In the context of ecology, Islam offers the concepts of theocentrism and theocentrism of humanism simultaneously. Theocentrism is a view that places humans as God’s chosen creatures whose totality of life must be shown to servitude (habl min Allah). The position of the universe is as a support in the process of servitude. Internal factors are caused by the imbalance of the environment itself. Meanwhile, external factors are caused by human actions that do not maintain the balance of the environment. Both of these factors can cause damage that has an impact on human and environmental losses as well as other factors such as economy, development, education and so on. The damage caused by the environment itself can cause disaster for humans. Meanwhile, environmental damage caused by greedy human actions can be a punishment for humans. To overcome environmental damage, there are several solutions, namely faith and piety, environmental awareness and sustainable management of the natural environment.